PENGARUH KEAMANAN BERTRANSAKSI, KEMUDAHAN PENGGUNAAN, DAN PERSEPSI RISIKO TERHADAP MINAT BELI SECARA ONLINE DI SITUS E-COMMERCE LAZADA (Studi pada Pengguna Situs Lazada.id di Kota Semarang) - Yulia Rozana; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
Abstract Internet users in Indonesia are growing every year. Along with the development of the internet, the development of online shoping activities also evolved over time shifted some direct transaction activities. Based on the results of calculation analysis using SPSS for windows version 20 can be explained that the results of direct impact test on this research model showed the results of positive and significant influence. All X variables have an influence on variable Y. Based on this, the researcher suggested to add and maximizing innovation in generating features related to transaction security, ease of use, and risk perception in order to maximize consumer buying interest